Decent work, work motivation and psychological capital: An empirical research - Ferraro, Tânia (2019)
BACKGROUND: The Decent Work (DW) concept, proposed by the International Labour Organization, can be enriched by the contributions of a Work, Organizational and Personnel Psychology (WOPP) perspective. Namely, it would be important to relate DW perceptions to the main concepts in the WOPP realm. Understanding these relations would expand our knowledge of the nomological network of the DW concept and of its practical implications. OBJECTIVE: To analyze the relationships between DW, work motivation and psychological capital among knowledge workers in Portugal and Brazil. METHODS: The Decent Work Questionnaire (DWQ), a previously validated measure of 7 dimensions of DW from a WOPP perspective, the Multidimensional Work Motivation Scale (MWMS), and the Psychological Capital Questionnaire (PCQ) were administered to 2912 knowledge workers. Relations among concepts were analyzed by canonical correlation analyses and linear regression. RESULTS: The DW dimension Fulfilling and Productive Work was positively associated with intrinsic and identified work motivation, and negatively with amotivation. A second significant canonical variate related (negatively) Social Protection (DW dimension) to extrinsic material work motivation. Results from regression analysis support the idea that DW promotes psychological capital. CONCLUSIONS: Results suggest that DW is an important predictor of work motivation and psychological capital. Practical implications for human resources management are presented.